COVID - 19 and Disparities in India : An Analysis - Mahajan, Ashwani; Chand, Phool (Prabandhan: Indian Journal of Management, 2022)
COVID-19 has been no less than a nightmare for the world. No community or person was left unaffected. The impact of the coronavirus pandemic can be seen in different sections of society, but this impact has not been uniform for all. The current pandemic has amplified the inequalities that were somehow already deep-rooted across the globe. For a country like India too, where inequalities had been acting as impediments for individuals and communities, preventing them from playing pivotal roles in social, economic, and political life, the emergence of the coronavirus pandemic has widened these inequalities. The present paper studied the disparities in India, amplified during COVID-19, considering some important sectors like health and education that played a crucial role in building the country’s social infrastructure. Also, other variables like income, GDP, poverty, unemployment, and gender inequality have also been taken into consideration to understand the intertwined and magnified impact of the coronavirus pandemic on widening the socio-economic gap. This paper found that in India and many parts of the world, efforts to move towards self-reliance is the right approach, as the same would help us reduce inequalities by creating employment and incomes.